PENGARUH CITRA MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK LE MINERAL DI TANGERANG - fahrezi, ahmad; Guston Sitorus; Noviarti (Jurnal Satya Mandiri Manajemen dan Bisnis, 2024)
This research aims to determine the influence of brand image, price and promotion on the decision to purchase bottled drinking water from the Le Mineral brand in South Tangerang. This research design uses casual quantitative. The population in this study was all Le Mineral agents in South Tangerang totaling 253 agents, while the sample used was 155 respondents. The data analysis method uses Multiple Linear Regression and SPSS 27 software. The results of this research are that Brand Image, Price and Promotion have a positive and significant effect on Purchase Decisions of Le Mineral Brand Bottled Drinking Water in South Tangerang. Brand image has a positive and significant effect on the decision to purchase packaged drinking water from the Le Mineral brand in South Tangerang. Price has a positive and significant effect on the decision to purchase packaged drinking water from the Le Mineral brand in South Tangerang. Promotion has a positive and significant effect on the decision to purchase packaged drinking water from the Le Mineral brand in South Tangerang.